Sintering characteristic, microstructure and microwave dielectric properties of the borax-added Sr3(VO4)2 ceramics. Issue 2 (15th January 2021) - Yao, Pengyu; Deng, Yaping; Li, Bo
Abstract: Na2 B4 O7 ·10H2 O (borax) doped Sr3 (VO4 )2 ceramics for ULTCC applications were synthesized by the solid-state reaction. The influence of borax addition on the sintering characteristic, microstructure, and microwave dielectric properties of Sr3 (VO4 )2 ceramics was investigated in detail. The result indicated that borax was an effective sintering aid for the Sr3 (VO4 )2 system and a suitable amount of borax dramatically reduced the sintering temperature of Sr3 (VO4 )2 ceramics from 1000 to 675 °C. Meanwhile, borax addition prevented the Q × f value from getting degenerated and improved the τ f value of Sr3 (VO4 )2 ceramics in the case of ultra-lower sintering temperatures. Novel Sr3 (VO4 )2 + 1 wt% borax ceramic sintered at 675 °C with optimum properties of Q × f = 19, 200 GHz, ε r = 15.9, and τ f = 10.9 ppm/°C was achieved in this study.